Plasmodium infection fully activates the immune system in peripheral blood and tumor microenvironment in a murine Lewis lung cancer model - Huang, Qunfeng; Yang, Dongheng; Tao, Zhu; Yu, Zhaoqing; Ding, Wenting; Tao, Na; Liao, Xiulin; Lin, Haoxin; Cheng, Zhipeng; Gao, Susu; Kang, Zhongkui; Xie, Jianming; et al. (Frontiers in Molecular Biosciences, 2026)
BackgroundPlasmodium infection has been proven to activate antitumor immune responses. This study comprehensively analyzes the immune cell populations in peripheral blood and tumor microenvironment to elucidate the potential immunological mechanisms by which Plasmodium infection inhibits tumor growth.MethodsWe established a subcutaneous Lewis lung cancer model in C57BL/6J mice and treated them with intraperitoneal injection of Plasmodium yoelii. The long and short diameters of tumors were measured. Then, high-dimensional flow cytometry was used to analyze the T cell subsets, macrophages and myeloid-derived suppressor cells (MDSCs) in peripheral blood and tumor tissues. Immunosuppression-related phosphorylated signal transducer and activator of transcription 3 (pSTAT3) and TGFβ in tumor tissues were also measured through Western blotting assay.ResultsPlasmodium infection inhibited the growth of Lewis lung cancer in mice. The infection increased in the numbers of CD3+ T cells, including CD4+ and CD8+ T, CD4+ central memory T (Tcm), CD4+ effector memory T (Tem), CD8+ Tcm, CD8+ Tem, CD8+ virtual memory T (Tvm), CD8+ short-lived effector cells (SLEC), and CD8+ memory precursor effector cells (CD8+ MPEC) in peripheral blood. Concurrently, the infection also increased the numbers of CD3+ T cells, including CD4+ and CD8+ T, CD4+ Tcm, CD4+ Tem, CD4+ tissue resident memory T (Trm), CD8+ Tcm, CD8+ Tem, CD8+ Trm and CD8+ SLEC in tumor tissues. In addition, Plasmodium infection reduced the expression levels of PD-1 on CD4+ and CD8+ T, the number of polymorphonuclear MDSCs, and increased the ratio of M1/M2 macrophages in the tumor tissues. The initial mechanism study revealed that Plasmodium infection significantly reduced the expression levels of pSTAT3 and TGFβ in tumor tissues, providing direct evidence that Plasmodium infection activated the antitumor immune responses.ConclusionBased on our past and current studies, we can draw the following conclusion: Plasmodium infection fully remodels and activates the immune system, targets and inhibits the entire tumor ecosystem through the key signals of pSTAT3 and TGFβ. This is completely different from the mechanisms of action of the current immune checkpoint blockade therapies, representing a new form of cancer immunotherapy, namely, the immune ecotherapy.